Drivers and Barriers of Science Teacher Development Program on STEM Learning Using Arduino - Sarah, Lia Laela; Nahadi, Nahadi; Sriyati, Siti (Jurnal Pijar Mipa, 2024)
The science teacher development program on STEM Learning using Arduino was conducted to enhance science teacher competencies in designing and implementing a 21st-century skills-based teaching approach. This study implemented research evaluation with Context, Input, Process, and Product (CIPP) to determine the drivers that supported and enhanced the program's effectiveness and address the barriers that obstruct teachers' competencies. The methodology employed in this study is both qualitative and quantitative methods. Qualitative methods gather data through observations, interviews, and document analysis. In addition, quantitative methods involve calculating the percentage of participants who complete the training program. Interviews and document studies in context evaluation help determine if program objectives are relevant to teachers' needs and aligned with the curriculum. Observation, interview, and document study were employed to evaluate input, process, and product and complement with quantitative data. The result shows that the science teacher development program is highly relevant today in enhancing teachers' competencies to design 21st-century skills-based teaching. However, some improvements are still needed to support the drivers and eliminate the barriers to make the program more effective. Some drivers, such as participants' motivation, well-organized content, competent facilitators, and sufficient resources, are assets to continue the program. However, the revision of the indicator objectives program, the selection process of participants, the time to conduct the workshop session, guidance, and content representation are essential to note.